Classification of microbial α‐amylases for food manufacturing using proteinase digestion. Issue 5 (11th June 2014) - Akiyama, Takumi; Yamazaki, Takeshi; Tada, Atsuko; Ito, Yusai; Otsuki, Noriko; Akiyama, Hiroshi
Abstract Enzymes produced by microorganisms and plants are used as food additives to aid the processing of foods. Identification of the origin of these enzyme products is important for their proper use. Proteinase digestion of α‐amylase products, followed by high performance liquid chromatography (HPLC) analysis, was applied to α‐amylase from the mold Aspergillus species, the bacteria Bacillus species, and the actinomycetes Saccharomonospora species. Eighteen commercial products of α‐amylase were digested with trypsin and endoproteinase Lys‐C and HPLC analyzed. For some proteinase/sample combinations, the area of the intact α‐amylase peak decreased and new peaks were detected after digestion. The presence and retention times of the novel peaks were used to group the products. The results from this method, called the proteinase digestion–HPLC method, allowed the classification of the α‐amylase products into 10 groups, whereas the results from sodium dodecyl sulfate polyacrylamide gel electrophoresis allowed their classification into seven groups.